Building Social Capital from the Inside Out: Leveraging Intrapower (Personal Capital) - Haynes, Norris M. (Social Capital and Community Well-Being : The Serve Here Initiative, 2016)
In this writer’s view, the building of social capital starts with the development of personal individual capital. The author posits that an individual may not be optimally effective in building meaningful social relationships and networks, or in influencing results in one’s community that serve the individual and others well, unless the individual has the prerequisite personal attributes and skillsets to do so. Therefore, in this chapter, the author identifies four key personal capital attributes that he sees as foundational to the building of social capital from the inside out. The dynamic synergistic interface among these four core attributes (Control, Empathy, Awareness, and Resolve), is referred to in this chapter as “Intrapower that is seen as a potent facilitative force in the effective building of social capital.
Citation Key Alias: lens.org/047-450-620-848-381
Keywords: Achievement motivation; Civic engagement; Mindfulness; Resilience; Self-awareness; Self-control; Self-regulation; Social & emotional; Youth development; dept.edl